2016
DOI: 10.1111/1348-0421.12447
|View full text |Cite
|
Sign up to set email alerts
|

Killer immunoglobulin‐like receptor repertoire analysis in a Caucasian Spanish cohort with inflammatory bowel disease

Abstract: Immunological molecules are implicated in inflammatory disorders, including inflammatory bowel disease (IBD; Crohn disease [CD] and ulcerative colitis [UC]). Killer cell immunoglobulin-like receptors (KIRs) are also genetically variable proteins involved in immune function. They are expressed by NK cells and certain T lymphocytes, regulate specificity and function by interaction with HLA Class I molecules, may be either inhibitory or activating and are polymorphic both in terms of alleles and haplotype gene co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…This reaction produces a color signal that is detected by the analyzer Luminex. Analysis of all signals from the responding probes in special program allows to obtain the result of KIR genotyping on intermediate resolution ( Figure 5 ) [ 38 , 39 ].…”
Section: Kir Typing Methodsmentioning
confidence: 99%
“…This reaction produces a color signal that is detected by the analyzer Luminex. Analysis of all signals from the responding probes in special program allows to obtain the result of KIR genotyping on intermediate resolution ( Figure 5 ) [ 38 , 39 ].…”
Section: Kir Typing Methodsmentioning
confidence: 99%
“…Among inhibitory KIRs, KIR2DL1 recognizes group 2 HLA-C (HLA-C2) molecules, which have lysine at position 80, KIR2DL2 and KIR2DL3 recognize group 1 HLA-C (HLA-C1) having asparagine at position 80, and KIR3DL1 recognizes HLA-Bw4 [ 2 6 ]. Although several studies have demonstrated that KIR-HLA receptor-ligand combinations are associated with IBD [ 7 12 ], discrepancies in the literature exist. KIR genes have not been evaluated in Japan to date.…”
Section: Introductionmentioning
confidence: 99%
“…The eQTL analysis showed that one of the SNPs, rs11672983, was associated with the expression of genes within the KIR gene complex. In line with this finding, Lopez-Hernandez et al [48] identified KIR2DS1 and KIR2DS5 as significant risk factors in Spanish IBD patients. Taken together, the studies suggest that imbalances between activating and inhibitory KIR genes and their ligands may explain, at least in part, the pathogenesis of the inflammatory bowel diseases.…”
Section: Discussionmentioning
confidence: 57%